2017
DOI: 10.1016/j.jpeds.2016.10.065
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Methods at Discharge Predict Long-Term Feeding and Neurodevelopmental Outcomes in Preterm Infants Referred for Gastrostomy Evaluation

Abstract: Objective To test the hypothesis that oral (PO) feeding at first neonatal intensive care unit (NICU) discharge is associated with less neurodevelopmental impairment and better feeding milestones, as compared with discharge with a gastrostomy tube (g-tube). Study design We studied outcomes for a retrospective cohort of 194 neonates < 37 weeks gestation referred for evaluation and management of feeding difficulties between July 2006–July 2012. Discharge milestones, length of hospitalization, and Bayley Scales … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
66
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 33 publications
4
66
0
2
Order By: Relevance
“…There continued to be a significant difference in the ability to orally feed in the HLHS‐NEC infants compared with the HLHS‐nNEC infants at time of their second surgery. This is consistent with data in noncongenital heart disease patients that documented route of feeding at time of initial hospital discharge predicting long‐term feeding difficulties . As stated before, infants with congenital heart disease have underlying issues that place them at increased risk for feeding issues, but the inability to orally feed may have cognitive, communication, and motor implications in these patients .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…There continued to be a significant difference in the ability to orally feed in the HLHS‐NEC infants compared with the HLHS‐nNEC infants at time of their second surgery. This is consistent with data in noncongenital heart disease patients that documented route of feeding at time of initial hospital discharge predicting long‐term feeding difficulties . As stated before, infants with congenital heart disease have underlying issues that place them at increased risk for feeding issues, but the inability to orally feed may have cognitive, communication, and motor implications in these patients .…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with data in noncongenital heart disease patients that documented route of feeding at time of initial hospital discharge predicting long-term feeding difficulties. 34 As stated before, infants with congenital heart disease have underlying issues that place them at increased risk for feeding issues, but the inability to orally feed may have cognitive, communication, and motor implications in these patients. 25,26,34 Though presence of NEC was associated with increased unadjusted odds of not being fed orally, adjusted odds ratio found that NEC was not necessarily a significant risk factor.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Placement of gastric tubes during infancy may have been more common in the children with ventricular shunts and BPD, due in part to their greater likelihood of neurodevelopmental delay and dysphagia. A recent study found that preterm infants who needed gastric tube placement prior to discharge from the NICU, were more likely to have a severe IVH and to have neurodevelopmental delay at 18‐24 months of age . Another study evaluating children at risk for dysphagia found that aspiration, gastro‐esophageal reflux, and age one year or less were significant risk factors for subsequent pneumonia .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that preterm infants who needed gastric tube placement prior to discharge from the NICU, were more likely to have a severe IVH and to have neurodevelopmental delay at 18-24 months of age. 18 Another study evaluating children at risk for dysphagia found that aspiration, gastroesophageal reflux, and age one year or less were significant risk factors for subsequent pneumonia. 19 It is possible that early gastric tube placement and/or Nissen fundoplication in our study population may have mitigated the potential adverse effects of dysphagia and aspiration on long-term respiratory outcomes in the VS children.…”
Section: Discussionmentioning
confidence: 99%